Developing smart fractions as a learning media assisted by ispring suite 9 and geogebra for escalating students’ computational thinking skills - Rafiantika Megahnia Prihandini; Dafik Dafik; Dahri Novan Uji Iskandar (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
In the era of the Industrial Revolution 4.0, learning mathematics puts more demands on students’ computational thinking skills. This research responds to this challenge by developing learning media assisted by iSpring Suite 9 and GeoGebra Software, known as the Smart Fractions. This development method employed Borg and Gall’s ten-stage method. These stages included preliminary research, product planning and development, preliminary product design, product validation, preliminary product revision, user trial, product revision, effectiveness tests, final product and mass production, and product dissemination and implementation. The research data corroborated the validity, effectiveness, and practicality of the Smart Fractions interactive learning media. Media experts, material and learning experts, and students as users have acknowledged these properties. A validity test demonstrated a value of V_a = 3.53, which implied a decent extent of validity. The practicality test through questionnaire and observation generated a practicality score of 86.67%, another decent product property. The product's effectiveness was tested by assessing students’ learning outcomes, which indicated an N-Gain score of 0.8. This inferred a noteworthy increase in computational thinking skills after implementing learning media. A t-test (2-tailed) also confirmed a significant difference in students' computational thinking skills before and after using learning media, as indicated by p = 0.000. The findings have concluded that Smart Fractions is a highly appropriate learning medium to improve students' computational thinking skills and help them visually understand fractions. The recommendation is to encourage students to use the learning media with the aid of manuals and tutorials on using the media. Teachers are also advised to combine the media with appropriate models, methods, strategies, and approaches.